Typification of names in Amaranthus (Amaranthaceae) described by Sennen from Spain - Mestre, Edgard; Sáez, Llorenç; Nualart, Neus (Phytotaxa, 2021)
The names in Amaranthus described by Frère Sennen from Spain were studied and, when necessary, typified. Seventeen lectotypes, preserved in BC and MA herbaria, have been designated. Isolectotypes were traced at BCN, herb. Sennen II, JE, JBAG (herb. Laínz), K, MA, P, and PH.